Effect of fluorine substituents on benzothiadiazole-based D–π–A′–π–A photosensitizers for dye-sensitized solar cells. Issue 16 (3rd March 2020) - Li, Shuping; Yang, Xichuan; Zhang, Li; An, Jincheng; Cai, Bin; Wang, XiuNa
Abstract : The results and interpretations can clearly explain the reasons for the poor photovoltaic performance of DFBT in DSSCs. Abstract : Two D–π–A′–π–A organic dyes with triazatruxene (TAT) as the electron donor, thiophene as the π-spacer, benzoic acid as the anchor group, and benzothiadiazole (BT) or difluorobenzo[ c ][1, 2, 5]thiadiazole (DFBT) as the additional acceptor, namely LS101 and LS102, respectively, were applied to dye-sensitized solar cells (DSSCs). As fluorine substituents are usually strong electron-withdrawing groups, introducing two fluorine atoms into BT was expected to strengthen the electron-withdrawing ability of the auxiliary acceptor, resulting in DSSCs with a broader light capture region and further improved power conversion efficiency (PCE). Fluorine is the smallest electron-withdrawing group with an induction effect, but can also act as an electron-donating group owing to its conjugation effect. When the conjugation effect is dominant, the electron-withdrawing ability of additional acceptor DFBT decreases instead. Accordingly, the band gap of LS102 was broadened and the UV-vis absorption spectrum was blue-shifted. In the end, DSSCs based on LS101 achieved a champion PCE of 10.2% ( J sc = 15.1 mA cm −2, V oc = 966 mV, FF = 70.1%) while that based on LS102 gave a PCE of only 8.6% ( J sc = 13.4 mA cm −2, V oc = 934 mV, FF = 69.1%) under standard AM 1.5G solar irradiation (100 mW cm −2 ) with Co 2+ /Co 3+ as the electrolyte.